Analisis kesiapan UMKM berbasis indikator dalam mendukung implementasi digital traceability pada industri halal - Zahrina, Raudh; Sari, Novita; Rokhman, Fatkhur (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the readiness of SMEs based on indicators in supporting the implementation of digital traceability in the halal industry in Indonesia. Digital traceability has become a critical need as consumers increasingly demand transparency in production and distribution processes, as well as assurance of product halal status from source to market. This study employs a descriptive qualitative approach using a literature review method, analyzing five scientific articles that discuss the halal ecosystem, the halal supply chain, the digital transformation of SMEs, the readiness of the halal value chain, and storage technology systems in the halal sector. The results indicate that SME readiness can be measured through indicators such as production processes, halal certification, packaging, storage, distribution, digital technology, human resources, and policy support. The main challenges lie in low digital literacy, limited implementation costs, insufficient data integration, and inadequate technological infrastructure. However, significant opportunities arise from the increasing global demand for halal products, government regulatory support, and advancements in blockchain technology, the Internet of Things, and QR traceability systems. This study concludes that the implementation of digital traceability in halal SMEs requires collaboration among the government, certification bodies, business operators, and the Islamic finance sector to ensure the sustainable improvement of the national halal industry’s competitiveness.